Correction: Integrated Mendelian randomization and single-cell RNA-sequencing analyses identified OAS1 as a novel therapeutic target for erectile dysfunction via targeting fibroblasts - Wang, Yi; Chen, Guihua; Li, Deng (Biology direct, 2025)
Correction: Biology Direct (2024) 19:136 https://doi.org/10.1186/s13062-024-00587-7 After publication of the article, it was brought to our attention that the affiliation of author Guihua Chen and Deng Li need to be amended. Rights and permissions Open Access This article is licensed under a Creative Commons Attribution-NonCommercial-NoDerivatives 4.0 International License, which permits any non-commercial use, sharing, distribution and reproduction in any medium or format, as long as you give appropriate credit to the original author(s) and the source, provide a link to the Creative Commons licence, and indicate if you modified the licensed material. Copy to clipboard Provided by the Springer Nature SharedIt content-sharing initiative Correction Open access Published:23 January 2025 Correction: Integrated Mendelian randomization and single-cell RNA-sequencing analyses identified OAS1 as a novel therapeutic target for erectile dysfunction via targeting fibroblasts Yi Wang1,2 na1, Guihua Chen2 na1 & Deng Li 2 Biology Direct volume 20, Article number: 12 (2025) Cite this article Metrics details The Original Article was published on 24 December 2024 Correction: Biology Direct (2024) 19:136 https://doi.org/10.1186/s13062-024-00587-7 After publication of the article, it was brought to our attention that the affiliation of author Guihua Chen and Deng Li need to be amended.